Handling of Krueng Jantho Riverbed Degradation with Groundsill Planning - bravikawati, marini (Journal of The Civil Engineering Student, 2021)
Krueng Jantho river has an important role in the utilization of water resources, watershed conservation, and control of water damage. Dredging of river material has resulted in damage to the ecological factors of the Krueng Jantho river, specifically the degradation of the riverbed which can trigger the collapse of river banks and bridge pillars. The location under review is located in Alue Gintung Village, Seulimuem District, Aceh Besar Regency. Data and maps collected are watershed maps, river discharge data from the Krueng Aceh water level measurement post (AWLR), and topographical and river cross-section data. The method of calculating the generation of discharge data is used the Markov Chain method, the analysis of flood discharge plans using the Pearson Log type III distribution method, and the groundsill building planning for river bottom management and security. The groundsill building for the 25 yearly discharge is planned to be 80.00 m wide, groundsill 1,00 m high and 4.00 m thick groundsill lighthouse.